Composite Thin Film Obtained Using Tetraethoxysilane and Aimed at VOCs Detection - Hernandez, Leonardo F.; Lima, Roberto R.; Pecoraro, Édison [UNESP]; Rosim-fachini, Esteban; Da Silva, Maria L.P. (Trans Tech Publications, 2012)
The aim of this work was production of tetraethoxysilane (TEOS) plasma polymerized thin films and optimization of their physical-chemical characteristic for sensor development. The films were analyzed using several techniques. It was possible to produce composites (graphite clusters imbibed by silicon oxide film) made from only one reactant (TEOS). Deposition rate can vary significantly, reaching a maximum of 30 nm/min; cluster formation and their size widely depending on deposition parameters. The film surface was hydrophobic but can be wetted by organic compounds, probably due to carbon radicals. These films are good candidates for sensor development.
Keywords: Composite; Plasma deposition; TEOS